ANALYSIS OF THE ROLE OF COMMUNITY EMPOWERMENT INSTITUTIONS (LPM) IN DEVELOPMENT SUPERVISION IN KADING VILLAGE, TANETE RIAJA SUB-DISTRICT, BARRU DISTRICT - Wahyul A Z; Rosdiana; Wahyuddi (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal